2011
DOI: 10.3109/09638288.2011.556207
|View full text |Cite
|
Sign up to set email alerts
|

The effects of problem-solving skills training based on metacognitive principles for children with acquired brain injury attending mainstream schools: a controlled clinical trial

Abstract: The results of this study supported the use of explicit problem-solving skills training to improve daily functioning for children with ABI, and the need for a larger-scale, randomised controlled study with long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
0
28
0
1
Order By: Relevance
“…Chan and Fong (2011) reported that a metacognitive problem-solving skills-training program resulted in a significant improvement in parent ratings of their children's executive function difficulties relative to both baseline ratings and to a control group. A study of 14 preadolescents with TBI versus a matched injured control group showed improvements in several aspects of executive functioning, as rated by parents, following an intervention program involving social mediation, cooperative learning, and metacognitive learning (Braga, Rossi, Moretto, da Silva, & Cole, 2012).…”
Section: Adhdmentioning
confidence: 96%
“…Chan and Fong (2011) reported that a metacognitive problem-solving skills-training program resulted in a significant improvement in parent ratings of their children's executive function difficulties relative to both baseline ratings and to a control group. A study of 14 preadolescents with TBI versus a matched injured control group showed improvements in several aspects of executive functioning, as rated by parents, following an intervention program involving social mediation, cooperative learning, and metacognitive learning (Braga, Rossi, Moretto, da Silva, & Cole, 2012).…”
Section: Adhdmentioning
confidence: 96%
“…21 Problem-solving training has demonstrated promise in various clinical populations [22][23][24][25][26] ; however, it has only been preliminarily explored in pediatric TBI. [27][28][29][30][31][32][33][34] In a small randomized trial of children aged 5 to 17 years (N = 32), findings showed that family-centered online problem-solving therapy improved internalizing behavioral problems after severe TBI. 32 Initial evidence suggests that problem-solving interventions can also be delivered effectively through a web-based portal directly to children with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…These interventions were applied directly to the children in face-toface group sessions that took place twice a week. 68,69 Poor self-regulation in childhood is a predictor of a variety of mental health problems in adulthood. 8 Hence, it is important to find effective interventions to improve emotional, cognitive, and behavioral self-regulation in children with ABI.…”
Section: Disruptive Behavior At Schoolmentioning
confidence: 99%